What makes a good mother? An interpretative phenomenological analysis of the views of women with learning disabilities. (May 2017) - Kaspar, Phoebe; Kroese, Biza Stenfert
Abstract: Background: Parents with learning disabilities are at risk of having their children permanently removed. There are discrepancies between the perceived needs of these individuals as assessed by the parents themselves, compared to the professionals who support them. Little is known about how individuals with learning disabilities view 'good parenting'. Method: After gaining informed consent, semi-structured interviews were conducted with eight women with a learning disability. Interviews explored their view on what makes a good mother and resulting qualitative data were analysed using Interpretative Phenomenological Analysis. Results: Four super-ordinate themes were identified: 'Mother as provider', 'A two-way bond' 'Motherhood transcends boundaries' and 'The same as anybody else?' Discussion: Some sub-themes mirror principles of Attachment Theory (Bowlby, 1982) including reciprocity, proximity seeking and a close mutual bond. Participants are aware of stigma surrounding disability and parenting and may be at risk of internalising such views to the detriment of their psychological wellbeing.